Reactive power as an ancillary service. - Bhattacharya, K. (IEEE Transactions on power systems)
This paper addresses the problem of reactive power procurement by an independent system operator (ISO) in deregulated electricity markets. A reactive bid structure is proposed in the context of a reactive power market. Based on the reactive power price offers and technical constraints involved in reactive power planning, a two-tier approach is developed to determine the most beneficial reactive power contracts for the ISO. The reactive capability of a generator and therefore the opportunity costs in providing reactive power is also included in the model. Uncertainty in reactive demand and in reactive bids of participating parties is incorporated through Monte Carlo simulations and the expected reactive power procurement plan for the ISO is hence determined. The CIGRE 32-bus network, approximately representing the Swedish system, is used for the studies